2019
DOI: 10.1111/jsr.12942
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and neuropsychiatric disorders

Abstract: This last issue of JSR in 2019 encompasses many different topics from our field of sleep research and sleep medicine. A major focus this time will be work on sleep in neuropsychiatric disorders, encompassing original work and review articles. As this is the last issue for 2019, it seems timely to reflect on this year, which will soon give way to 2020. 2019 has seen a major increase in submissions for JSR and it is 2 of 2 | EDITORIAL still has to be considered preliminary, but it does suggest that sleep extensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Different thresholds have been proposed to classify insomnia according to ISI scores. According to a binary classification, scores of 10 or higher have been considered suggestive of the presence of insomnia symptoms in the general population [48], whereas introducing multiple thresholds led to a differentiation between the absence of insomnia (0-7); sub-threshold insomnia (8)(9)(10)(11)(12)(13)(14); and overt (moderate and severe) insomnia (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) [49]. It was validated for both adolescents (14-19 years) and adults (>19 years) [50].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different thresholds have been proposed to classify insomnia according to ISI scores. According to a binary classification, scores of 10 or higher have been considered suggestive of the presence of insomnia symptoms in the general population [48], whereas introducing multiple thresholds led to a differentiation between the absence of insomnia (0-7); sub-threshold insomnia (8)(9)(10)(11)(12)(13)(14); and overt (moderate and severe) insomnia (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) [49]. It was validated for both adolescents (14-19 years) and adults (>19 years) [50].…”
Section: Methodsmentioning
confidence: 99%
“…A significant number of clinical and epidemiological studies have highlighted that insomnia and medical conditions are exacerbated by each other in a vicious cycle [11][12][13][14][15][16][17], thus producing negative consequences on well-being [18]. In this context, it has been reported that chronic insomnia acts as a predisposing, precipitating and perpetuating factor for several medical conditions.…”
Section: Introductionmentioning
confidence: 99%